A Role of CXCL1 Drives Osteosarcoma Lung Metastasis via VCAM-1 Production - Lee, Chiang-Wen; Chiang, Yao-Chang; Yu, Pei-An; Peng, Kuo-Ti; Chi, Miao-Ching; Lee, Ming-Hsueh; Fang, Mei-Ling; Lee, Kuan-Han; Hsu, Lee-Fen; Liu, Ju-Fang (Frontiers in Oncology, 2021)
Osteosarcoma is a common aggressive and malignant cancer in the musculoskeletal system of young adults. Most frequently lung metastases are the main death reason for osteosarcoma. However, molecular mechanisms of metastasis involved in metastasis of osteosarcomas are still unclear. Recently, the chemokine, CXCL1, and its receptor, CXCR2, which have been suggested involving the directing of neutrophils into the tumor microenvironment, plays a crucial indicator for lung metastasis in osteosarcoma by paracrine releases. Here a higher expression of CXCL1 on osteosarcoma cell lines and positively correlated with the migratory and invasive activities. Furthermore, the CXCR2/focal adhesion kinase (FAK)/phosphatidylinositol-3-kinase (PI3K)/Akt pathway is activated by CXCL1 to promote vascular cell adhesion molecule 1 (VCAM-1) expression via upregulation of nuclear factor-kappa B (NF-κB) expression and nuclear translocation ability. The in vivo animal model further demonstrated that CXCL1 is a critical promoted factor for osteosarcoma metastasis to the lung. A positive correlation in CXCL1 and VCAM-1 expression was observed in the immunohistochemistry staining of human osteosarcoma specimens. Our findings draw a cascade mechanism in the regulatory network for lung metastasis osteosarcoma and indicating the CXCL1/CXCR2 pathway is a worthwhile candidate for further developing treatment schemas.